NGHIÊN CỨU ẢNH HƯỞNG CỦA SINH VẬT BÁM BẨN TRONG MÔI TRƯỜNG NƯỚC BIỂN TỚI HIỆU QUẢ BẢO VỆ CHỐNG ĂN MÒN BẰNG PHƯƠNG PHÁP PROTECTOR - Mai, Văn Minh; Lê, Thị Mỹ Hiệp; Phan, Bá Tứ (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDYING ON THE IMPACT OF BACTERIA IN THE SEA WATER TO ANTI-CORROSION PROTECTIVE EFFICIENCY OF THE METHOD USING PROTECTOR The use of zinc protector for corrosion protection against steel and alloys in seawater are usually calculated according to the major technical parameters including electrochemical equivalent, location, shape, size and weight. However, in tropical marine environmental conditions, bio-fouling is participated. They grew very quickly and covered the entire surface of both the protector and materials and caused physical barriers which affect the material protection. The study was done in natural seawater and sterilized seawater in 12 months. The results indicate that bio-fouling strongly affected the corrosion rate of mild steel in seawater. However it also indicated that the zinc-based protector still guarantees protection effectivity even when it was completely coated by macrofoulers. In addition, at two months time point, the biomass on the protected samples was less than that compared to the unprotected samples. This can be explained by the fact that the sample surface is smoother (due to less corrosion) and therefore marine organisms are more difficult to foul. The effects of biofouling on the corrosion rate of protected mild steel samples by zinc protector are negligible.